Survey on artificial intelligence based techniques for emerging robotic communication - Alsamhi, S. H.; Ma, Ou; Ansari, Mohd. Samar (Telecommunication systems, 2019)
This paper reviews the current development of artificial intelligence (AI) techniques for the application area of robot communication. The research of the control and operation of multiple robots collaboratively toward a common goal is fast growing. Communication among members of a robot team and even including humans is becoming essential in many real-world applications. The survey focuses on the AI techniques for robot communication to enhance the communication capability of the multi-robot team, making more complex activities, taking an appreciated decision, taking coordinated action, and performing their tasks efficiently. We present a comprehensive review of the intelligent solutions for robot communication which have been proposed in the literature in recent years. This survey contributes to a better understanding of the AI techniques for enhancing robot communication and sheds new lights on future research direction in the subject area.